2015
DOI: 10.1002/jssc.201500777
|View full text |Cite
|
Sign up to set email alerts
|

Matrix solid-phase dispersion coupled with homogeneous ionic liquid microextraction for the determination of sulfonamides in animal tissues using high-performance liquid chromatography

Abstract: Matrix solid-phase dispersion coupled with homogeneous ionic liquid microextraction was developed and applied to the extraction of some sulfonamides, including sulfamerazine, sulfamethazine, sulfathiazole, sulfachloropyridazine, sulfadoxine, sulfisoxazole, and sulfaphenazole, in animal tissues. High-performance liquid chromatography was applied to the separation and determination of the target analytes. The solid sample was directly treated by matrix solid-phase dispersion and the eluate obtained was treated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Reported novel solid-phase sorbent materials include MWCNTs utilized in a SPE protocol [43], and Fe 3 O 4 @JUC-48 nanocomposite utilized in a MSPE protocol [44]. An ionic liquid application was also reported in a MSPD-HILME protocol [46]. SPE [55], MSPE [57], and ATPS extraction [53,54] were the most reported approaches for the extraction of SAs from milk samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported novel solid-phase sorbent materials include MWCNTs utilized in a SPE protocol [43], and Fe 3 O 4 @JUC-48 nanocomposite utilized in a MSPE protocol [44]. An ionic liquid application was also reported in a MSPD-HILME protocol [46]. SPE [55], MSPE [57], and ATPS extraction [53,54] were the most reported approaches for the extraction of SAs from milk samples.…”
Section: Discussionmentioning
confidence: 99%
“…Other reported approaches included a combined MSPD-homogeneous ionic liquid microextraction (HILME) protocol for the extraction of seven SAs from bovine, chicken, and pork tissue samples [46], an on-line SPME protocol for the extraction of five antimicrobials, including sulfametoxydiazine, sulfamethoxazole, and SQX from chicken and pork tissue and egg samples [47] and a SBSE protocol for the extraction of ten SAs from chicken and pork tissue samples [48]. For the MSPD-HILME protocol, the ionic liquid employed acted both as elution solvent in MSPD and extraction solvent in HILME.…”
Section: Spementioning
confidence: 99%
See 1 more Smart Citation
“…They are also time consuming and usually have a high false positive rate. With recent advances in chromatographic and spectroscopic techniques, HPLC [10,11], LC-MS [12,13], LC-MS/MS [14][15][16][17][18][19][20], and LC coupled to high-resolution MS [21,22] have become prevalent. Generally, antimicrobial residues in animal-derived food are present in trace levels (ng/g).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SAs showed many side effects such as causing allergic hypersensitivity reactions and carcinogen resulting in hypothyroid . In recent years, SAs have been frequently detected at considerably high concentrations in environmental water and food samples by using HPLC–MS , UV‐Vis , fluorescence , and CE method. The sensitivity of modern analysis instruments has been improved, yet it is still difficult to obtain accurate results due to the interferences from sample matrix, especially for food samples.…”
Section: Introductionmentioning
confidence: 99%